Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/15548627.2019.1695399
|View full text |Cite
|
Sign up to set email alerts
|

The GID ubiquitin ligase complex is a regulator of AMPK activity and organismal lifespan

Abstract: The AMP-activated protein kinase (AMPK) regulates cellular energy homeostasis by sensing the metabolic status of the cell. AMPK is regulated by phosphorylation and dephosphorylation as a result of changing AMP/ATP levels and by removal of inhibitory ubiquitin residues by USP10. In this context, we identified the GID-complex, an evolutionarily conserved ubiquitin-ligase-complex (E3), as a negative regulator of AMPK activity. Our data show that the GID-complex targets AMPK for ubiquitination thereby altering its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 55 publications
(67 reference statements)
1
58
0
Order By: Relevance
“…CRL4 catalyzed ubiquitination also directs AMPKγ proteolysis [121]. GID ubiquitin ligase mediates ubiquitination and degradation of AMPK as well, leading to decreased autophagy and increased mTOR activity [122]. Ubiquitination of AMPKα can be reversed by USP10 to remove the ubiquitin chain from AMPKα and promote AMPK activation [122].…”
Section: Ubiquitination Of Ampkmentioning
confidence: 99%
“…CRL4 catalyzed ubiquitination also directs AMPKγ proteolysis [121]. GID ubiquitin ligase mediates ubiquitination and degradation of AMPK as well, leading to decreased autophagy and increased mTOR activity [122]. Ubiquitination of AMPKα can be reversed by USP10 to remove the ubiquitin chain from AMPKα and promote AMPK activation [122].…”
Section: Ubiquitination Of Ampkmentioning
confidence: 99%
“…Sex-specific methylation is also seen at this probe location in mouse muscle but in neither sheep or mouse blood (Figure 6A-B), implying that such androgen-sensitive effects in MKLN1 and other loci may be mammalian wide but certainly not ubiquitous across all tissues. Evidence for MKLN1 androgen-dependency has previously been presented (Jin et al, 2013) and MKLN1-containing complexes have been shown to regulate lifespan in Caenorhabditis elegans (Hamilton et al, 2005; Liu et al, 2019), although no links between this gene and mammalian longevity have yet been reported. ChIP-seq data demonstrates enriched AR binding at the position of this asDMP in human, as well as exhibiting high sequence conservation, DNase hypersensitivity and H3K27ac marks – the latter two of which are markers of open chromatin and indicate transcriptionally active areas (Figure 5C) (Creyghton et al, 2010; Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, MKRN1-null mice exhibit AMPK hyperactivity in liver and adipose tissue and are protected against diet-induced metabolic syndrome, whereas lowering MKRN1 expression in obese mice reversed non-alcoholic fatty liver disease. The glucoseinduced degradation deficient (GID)-protein complex has been reported to directly polyubiquitinate α-subunits via K48 linkages, to induce both AMPK proteasomal degradation and suppress activity as protective mechanisms to down-regulate autophagy during periods of prolonged nutrient starvation [113]. Intriguingly, α-T172 phosphorylated AMPK appeared to be the preferred substrate for GID ubiquitination, suggesting significant conformational rearrangement upon activation to enhance exposure of the target α-Lys residue.…”
Section: Ubiquitinationmentioning
confidence: 99%